2006
DOI: 10.1007/s11199-006-9104-1
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Homologous Reproduction in the Representation of Assistant Coaches of Women’s Teams

Abstract: Researchers (e.g., Stangl & Kane Sociology of Sport Journal, 8: 47-60, 1991) have been successful in using homologous reproduction theory to explain the decline of women in coaching roles. In this investigation, we aimed to extend previous research by exploring the practice in (a) employment patterns of assistant coaches, and (b) environments in which women are actually the dominant gender doing the hiring. Data from the 2002-2003 Equity in Athletics Disclosure Act (EADA) was used to determine if a head coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
1
29
0
2
Order By: Relevance
“…As mentioned at the onset of this article, Sagas et al (2006) recently found men did not engage in homosocial reproduction in sports by hiring more male than female assistants. Nonetheless, female assistants to male head coaches are apt to receive less mentoring (particularly psychosocial) than those who assist female head coaches.…”
Section: Practicalmentioning
confidence: 91%
See 1 more Smart Citation
“…As mentioned at the onset of this article, Sagas et al (2006) recently found men did not engage in homosocial reproduction in sports by hiring more male than female assistants. Nonetheless, female assistants to male head coaches are apt to receive less mentoring (particularly psychosocial) than those who assist female head coaches.…”
Section: Practicalmentioning
confidence: 91%
“…Unfortunately, this could impact women adversely because at least some research suggests mentoring has a disproportionately larger effect on career success for women than for men (Lockwood 2006;Noe et al 2002;Tharenou 2005). Thus, despite appearing equally likely to hire assistants of either sex (Sagas et al 2006), male coaches may provide less mentoring to their female assistants who appear to need it more.…”
Section: Introductionmentioning
confidence: 99%
“…Within this network White males tend to associate, mentor, and eventually hire people with whom they most closely identify. This process is also known as "homologous reproduction" and may limit the opportunities for minorities as they are not welcomed into this network (Cunningham & Sagas, 2006;Sagas, Cunningham, & Teed, 2006;Greenhill, Auld, Cuskelly, & Hooper, 2009). Further, as males have historically held roles of power, the masculine traits are more highly valued (Connell & Messerschmidt, 2005).…”
Section: Lack Of Racial Diversitymentioning
confidence: 99%
“…As people generally have more positive attitudes toward and prefer to interact with people similar to the self (in-group members) relative to those who are different (out-group members), intergroup bias can result. Illustrative of these dynamics, exercise class participants (Cunningham, 2006) and track-and-field coaches (Cunningham, 2007) who differ from others in their groups are likely to experience less satisfaction with and attachment to those entities.…”
Section: Racial Identitymentioning
confidence: 99%
See 1 more Smart Citation